Implementación del servicio de radio de la Universidad Nacional de Loja para los medios de difusión digital y dispositivos móviles. - Neira Balcázar, Jonathan Ezequiel (2017)
This present degree work is the result of the implementation of a streaming transmission system for the Universitary Radio that allows the encoding and distribution of its content in audio digital in web browsers. It provides a greater coverage of transmission to the radio listeners. In addition, a multi-platform mobile application is developed to access the streaming. The Barbara Kitchenham methodology is used for the analysis and selection of tools to the implementation of streaming, Once, it was Implemented through the server tools Icecast2, Butt Broadcast customer, MP3 codec and a minimum bandwidth of 256 kbps to develop the communication between the client and the server. To carry out the mobile application, the Mobile-D agile development methodology is used in its five phases: exploration, initialization, production, stabilization and testing. Also, the Ionic framework is used in the encoding which uses HTML5, CSS and JavaScript.